Unpacking the agroclimatic challenges and determinants of sweetpotato seed conservation and multiplication strategies by smallholder farmers in Southern Ethiopia. Issue 2 (7th February 2022) - Biazin, Birhanu; Low, Jan W.; McEwan, Margaret A.; Brouwer, Robert; Cherinet, Mihiretu; Aragaw, Abiyot
ABSTRACT: Sweetpotato is increasingly important in sub-Saharan Africa due to its yield potential under sub-optimal growing conditions. But lack of planting material (seed) at the onset of the rains is a major constraint. This study examined smallholder strategies for sweetpotato seed conservation and multiplication, their agroclimatic determinants, and farmers' perceived drought risk at four sites (Dilla, Chuko, Hawassa, Sodo) in Ethiopia using informant interviews, a survey of 278 households, and agroclimatic statistics. Conservation practices were dictated by farming system and agroecological conditions. The long-term mean length of dry period when multipliers must conserve seeds ranged between 103 and 131 days across sites. Seed multipliers faced high uncertainty of rainfall onset that varied from the end of February to mid-May. Estimated probabilities of moderate and severe droughts affecting seed conservation ranged from 36–75%, and 15–58%, respectively. In drier sites, age of multiplier, land-holding size, sweetpotato production experience and access to extension were positively associated with being a vine multiplier. Knowledge of indigenous conservations strategies should inform seed system intervention design.